Qur'anic Education and Qira'at Methodology: Revealing the Characteristics of Imam Al-Bazy's Qira'at Shadzah in the Context of Learning - Hafid, Abdul Hamid; Nabilah, Is’ad Durrotun; Najakhah, Vina Umdatun (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study explores the unique characteristics of Al-Bazy's recitation path, specifically focusing on the recitation of the takbir after Surat Al-Duha until the end of the Qur'an. This Takbir, although considered weak by hadith scholars, is well-known among Qurra' and has a sanad that goes back to the Prophet Muhammad. This study identified three main types of Ta'at al-Bazy: 1) Ta'at beginning with madd letters (elongated vowels), 2) Ta'at with a correct sukun consonant, and 3) Ta'at that begins with a harakat. In addition, Al-Bazy's recitation differs from other scholars in terms of the lengthening of the letter "ta", which resembles madd in Qur'anic recitation, and the use of madd in "alif la nahiyah" and the emphasis on "ta" in washal position. The main objective of this study is to analyse the unique characteristics of Imam al-Bazy's qira'at and its pedagogical implications in Qur'anic education. Using a qualitative approach with a descriptive-analytical method, this study collected data from primary sources, such as the works of Sanaa Suliman Abu Sa'ilik, and secondary sources, including classical texts, scholarly journals, and Quranic references. The research utilises a historical-philosophical approach to understand the social, cultural, and religious factors that influenced Imam al-Bazy's readings. The results of this study provide a detailed analysis of the distinctive features of al-Bazy's recitation and highlight its pedagogical implications for Qur'anic teaching. This research contributes to the field of qira'at studies by offering new insights into the educational value of qira'at variations, enriching the understanding of Qur'ānic exegesis and its role in Islamic education.